MANAJEMEN SAMPAH BERBASIS SWAKELOLA DALAM MEMBANGUN GREEN INTERNATIONAL BUSINEES DISTRICT (GIBD) DI KAWASAN KEMAYORAN - Dwi Aprianto (FT-USNI, 2021)
The purpose of this study is to determine the patterns of self-managed waste management in building a Green International Business District in the Kemayoran area. The method used in this research is a survey with descriptive qualitative analysis. Data analysis in this study was carried out interactively which included: data presentation and drawing conclusions. The data used uses data from the results of collecting types of waste collection patterns, the research location is in the Kemayoran area, Central Jakarta, this research was carried out from March to July 2020. The land area of this study covers 454 ha and most of it is heterogeneous waste, almost 50% is green waste or regional waste that dominates, the rest is office and household waste, but there is something unique in this area's waste movement, because some of it is an active area for international events so the waste is the products of leftovers. The event is R3 (Reduce, Reuse, Ryclycle). The results of the study indicate that the background for the realization of community-based environmental management is the Kemayoran area, which is located in the center of the city, which often experiences floods. In terms of human resources, about 75%% are employed from residents around Kemayoran, so they can control their management every day. People who are empowered in waste management are able to organize joint activities to solve waste problems, and form awareness in responding to waste problems on the basis of common interests. The results of field observations show that waste is managed with a fairly good selection although there are still some patterns that still use the burning method, although the percentage is small. To support the government, the Area Management has tried to support the implementation of good waste management as regulated in Law no. 18 of 2008 concerning Waste Management. These implementing regulations are urgently needed for Area Managers in innovating to develop economic activities in waste management. In an effort to make this happen, various obstacles were encountered, including acts of vandalism and the public's lack of awareness in disposing of waste in its place.